Marine collagen: purification, properties and application - Barzkar, Noora; Sukhikh, Stanislav; Babich, Olga; Venmathi Maran, Balu Alagar; Tamadoni Jahromi, Saeid (Frontiers in Marine Science, 2023)
Collagens are abundant structural proteins found in connective tissues such as bones, swim bladder, skin, blood vessels, intestines, and cartilage. They make up around 30% of the total protein. The purpose of this paper is to provide a summary of the current knowledge about collagen isolated from marine organisms and its possible applications. Collagen is widely used in pharmaceuticals, food, biomedical and cosmetic industries due to its cell adhesion, biocompatibility, and safety properties. This review discusses various methods for extracting collagen from marine vertebrates and its physicochemical properties. Enzymatic extractions might be a more effective at extracting collagen than acidic extractions. Peptides derived from collagen hydrolysates have biological activity that promotes health and relieves symptoms caused by chronic diseases. Aquaculture can help with collagen availability but an integrated technology for processing raw materials is necessary to address the negative effects of production waste. Marine collagen has many benefits over terrestrial sources including its versatility in healing skin damage and slowing down the aging process. The advantages of marine collagen over terrestrial sources are discussed along with its potential biotherapeutic applications in bone and skin injuries. The development of effective cosmetic products can become a strategic direction for technological development.